The Impact of Employees’ Psychological Capital on Innovative Work Behavior: The Chain Mediating Effect of Knowledge Donating and Knowledge Collecting - Chen, Weijing; Zhu, Xiaoyun; Sun, Shan; Liao, Shudi; Guo, Zhiwen (Frontiers in Psychology, 2021)
This study aimed to test the mediating role of knowledge sharing, which includes two central processes of knowledge collecting and knowledge donating, in the relationship of psychological capital and innovative work behavior (IWB). The proposed theoretical framework was based on the theory of reasoned action (TRA) and social exchange theory (SET). In a field study, using a research sample of 345 valid leader-subordinate matching data, we tested three competitive models to explore the different mediating effects of knowledge collecting and donating. Results indicated that knowledge sharing mediated the relationship between psychological capital and IWB. Specifically, knowledge donating and knowledge collecting mediated the relations between psychological capital and IWB in sequence, and the indirect effect of knowledge collecting was also significant. From the perspective of knowledge sharing, the present study deeply analyzes the psychological processing mechanism of psychological capital on IWB, confirms the positive significance of knowledge donating on the individual level, and provides a new perspective for organizations to promote employees’ participation in knowledge sharing and stimulate their IWB.